THE OCCUPANTS’ VISUAL ACUITY AND PERFORMANCE: METHODS FOR MEASURING OCCUPANTS’ VISUAL AND WRITING PERFORMANCES IN DAYLIGHT SPACES - Elina, Mohd Husini; Raja Nur Syaheeza, Raja Mohd Yazit; Awangku Abdul Rahman, Awangku Yussuf (Scientific Academia Network (Scientiaca), 2021)
Acceptable illuminance level in spaces is essential for optimum task performance that requires visual efficiency such as reading and writing. Passive design strategies are developed to meet the occupants’ visual comfort such as optimizing the daylight source. Previous researcher highlighted the illuminance level in a space correlates with the occupants’ performance, where the illuminance level which is higher and lower than there commended by the guidelines decreases the overall performances of the respondents. The guidelines and standards highlighted the acceptable illuminance level in office and school are between 300 lux to 500 lux. Various methods have been developed to identify the reading and writing performances of occupants in relation to daylight and illuminance level. This paper aims to study suitable methods that can be developed in identifying the occupants’ reading and writing performances in daylight spaces. The most common method to measure the respondents’ writing performance is the speed (minute) and word per minute (wpm) of the respondents to complete the writing task such as Handwriting Speed Test (HST) and Detailed Assessment Speed Handwriting (DASH).Secondly is to explore the changes of illuminance level whether has relation to visual performance. Therefore, the visual test is conducted to identify the task performance within the range of acceptable illuminance level. The students achieved the high visual performance not at the recommended level of illuminance. The changes of illuminance level of30 percent had influenced the student’s visual performance. In order to control the lighting strategy, the lighting systems and sensors in learning spaces are suggested to stable the light intensity and contribute to energy consumption